Optimization of Urban Delivery Systems Based on Electric Assisted Cargo Bikes with Modular Battery Size, Taking into Account the Service Requirements and the Specific Operational Context - Giuseppe Aiello; Salvatore Quaranta; Antonella Certa; Rosalinda Inguanta (Energies, 2021)
The implementation of new forms of urban mobility is a fundamental challenge for improving the performance of city logistic systems in terms of efficiency and sustainability. For such purposes, the exploitation of electric vehicles is currently being investigated as an alternative to traditional internal combustion engines. In particular, the employment of lightweight electric cargo bikes is seen as an attractive possibility for designing improved city distribution systems. Such vehicles, however, present substantial limitations related to their endurance, speed, power, and recharging times; therefore, their configuration must be optimized considering the actual operational context and the specific characteristics of the service operated. This paper proposes the employment of modular electric cargo bikes for urban parcel delivery, with the possibility of customizing some features of the vehicle in order to optimize the performance of the system. This research initially focuses on the design of the modular vehicle and subsequently on the selection of the best configuration through a multi criteria decision method. A numerical application demonstrates the effectiveness of the approach proposed by analysing different design options and determining the most efficient solution in a specific context.